Analysis of defect generation in Ti–6Al–4V parts made using powder bed fusion additive manufacturing processes - Gong, Haijun; Rafi, Khalid; Gu, Hengfeng; Starr, Thomas; Stucker, Brent (Additive manufacturing, 2014)
Ti–6Al–4V parts made using additive manufacturing processes such as selective laser melting (SLM) and electron beam melting (EBM) are subject to the inclusion of defects. This study purposely fabricated Ti–6Al–4V samples with defects by varying process parameters from the factory default settings in both SLM and EBM systems. Process parameters are classified according to their tendency to create certain types of porosity. Finally, defect characteristics are discussed with respect to defect generation mechanisms; and effective process windows for SLM and EBM system are discussed.